PSYCHOLOGICAL CHARACTERISTICS IN PATIENTS WITH CHRONIC HEART FAILURE WAITING FOR HEART TRANSPLANTATION - R. Yu. Shindrikov; A. A. Velikanov; E. A. Demchenko; V. M. Tishkova; O. Yu. Shchelkova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Numerous studies have established the role of psychological factors in the development, treatment, prognosis of the cardiovascular diseases, as well as in formation of compliance and the quality of patients’ lives. However, few of any psychological studies of patients with chronic heart failure (CHF) waiting for transplantation were carried out, despite the obvious need for reliable psychosocial assessments in the preoperative period and development of psychological support programs. In view of the foregoing, a pilot screening study aimed at assessing the state of the cognitive and affective spheres, personal characteristics of patients with CHFwaiting for the HTas wellanalyzing the relationship between psychological, medical and biological characteristics of patients.Material and methods. 30 patients withCHF took part in the study at theFederal State-Funded Institution «Federal Almazov North-West Medical Research Centre» (Saint-Petersburg). The authors’ structured interviews and psychodiagnostic methods were used in the study: «The index of well-being», (WHO, 1999), «The Brief Neuropsychological Cognitive Examination» (BNCE), «The Zung Self-Rating Depression Scale» (SDS), «The State-Trait Anxiety Inventory» (STAI), «Test the Big Five» (BIG V). Statistical data processing was performed using the Mann–Whitney U criterion and the Spearman correlation (SPSS v. 20.0).Results. Absence of violations of cognitive functions was revealed in 23 % of respondents, mild degree of cognitive deficiency – in 60 %, average degree – in 17 %. The lowest average scores were obtained in the BNCE subtests, reflecting the success of active attention, visual-spatial memory, psychomotorics, abstract thinking.The average group index of depression was 45.9±7.2 (normative level). A detailed analysis showed that absence of signs of depression occurred in 74 % of patients, subdepression – in 23 %, moderately expressed depression – in 3 %. In the entire sample, the average level of situational anxiety prevailed (42.4±6.8) with personal anxiety (39.7±8.1). According to the averaged scales of the BIG V questionnaire, moderately pronounced extroversion features predominated in the patient’s personality structure. The relationship between BNCE indices and duration of chronic HF (r = –0.676, p <0.001) was revealed. A statistically significant reduction in the overall level of cognitive function in patients with concomitant diabetes mellitus was found in comparison with patients without it (U = 61) at p = 0.033; According to the data of SDS depressive symptoms in patients with IHD are more pronounced in comparison with patients with dilated cardiomyopathy U = 47 (p = 0.019).